Advancing information technology and financial intermediation - Pekka Mannonen (The Research Institute of the Finnish Economy (ETLA), 2001)
The whole financial sector has been under a remarkable structural change, and one of the major contributing forces has been the rapid advance in information processing based on digital technology. The purpose of this paper is to model the influence of advancing information and transaction technology on the financial markets and assess the consequent structural changes within the different forms of banking. The overall conclusion is that improving information technology increases the transparency of firms and the liquidity of capital market instruments. This development favors market-based finance at the cost of traditional financial intermediaries. Traditional bank lending will also benefit, but this benefit is not sufficient to compensate its losses to market-based finance. The welfare effects will be positive because now a smaller amount of profitable projects are rejected due to insufficient information and market transparency. – – Rahoitussektori kokonaisuudessaan on ollut voimakkaan rakennemuutoksen alaisena, jossa eräänä merkittävästi vaikuttavana taustavoimana on ollut digitaaliseen tietotekniikkaan perustuvan informaatioteknologian nopea kehittyminen. Tavoitteena on mallittaa informaatio- ja transaktioteknologian vaikutukset rahoitusmarkkinoille sekä arvioida tästä seuraavia rakennemuutoksia eri pankkitoiminnan muotojen suhteen. Yleinen johtopäätös tutkimuksessa on, että informaatioteknologia lisää yritysten läpinäkyvyyttä rahoitusmarkkinoilla sekä pääomamarkkinainstrumenttien likvidisyyttä. Tämä kehitys suosii markkinapohjaista rahoitusta perinteisen pankkitoiminnan kustannuksella. Myös tavanomainen pankkitoiminta hyötyy, mutta saavutetut hyödyt eivät riitä kompensoimaan sen menetyksiä markkinapohjaiselle rahoitukselle. Hyvinvointivaikutukset ovat positiivisia, koska nyt pienempi osa potentiaalisesti kannattavista projekteista tulee hylätyksi riittämättömän informaation ja markkinaläpinäkyvyyden vuoksi.
Keywords: 330; Financial intermediation; information technology; risk and liquidity; Rahoituksen välitys; informaatioteknologia; riski ja likvidisyys; Finanzintermediär; Bank; Strukturwandel; Informationstechnik